STRATEGIES OF ISLAMIC EDUCATIONAL INSTITUTIONS IN BUILDING GLOBAL AWARENESS - Wahyuni, Ana Dwi; Umar, M. Abdullah; Sibawaihi, Sibawaihi (Jurnal Asy-Syukriyyah, 2025)
Globalization presents opportunities and challenges for various aspects of life, including education. This research examines Islamic educational institutions' strategy for building global awareness. The method of writing articles uses the literature review method. The analysis used in this article is content analysis. The results of the research on the strategy of Islamic educational institutions by integrating global issues in the curriculum, using creative and innovative learning methods that can develop students' critical and creative thinking skills, encouraging students to be involved in international activities, creating an inclusive and multicultural learning environment, developing human resources, building strategic partnerships, utilizing digital technology wisely, strengthening the spirit of leadership, strengthening Islamic character, strengthening the alumni network, and improving the image of Islamic educational institutions.